2019
DOI: 10.3847/1538-4357/ab29e6
|View full text |Cite
|
Sign up to set email alerts
|

Energy-conserving Relativistic Corrections to Strong-shock Propagation

Abstract: Astrophysical explosions are accompanied by the propagation of a shock wave through an ambient medium. Depending on the mass and energy involved in the explosion, the shock velocity V can be non-relativistic (V ≪ c, where c is the speed of light), ultra-relativistic (V ≃ c), or moderately relativistic (V ∼ f ew × 0.1c). While self-similar, energy-conserving solutions to the fluid equations that describe the shock propagation are known in the non-relativistic (the Sedov-Taylor blastwave) and ultra-relativistic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For mildly relativistic shocks we expect the standard ST scaling to hold up to terms that are proportional to V 2 /c 2 ; Coughlin (2019) showed that the coefficient of proportionality multiplying this correction, σ, is a parameter that depends on the post-shock adiabatic index of the gas (effectively equal to 4/3) and the ambient density profile (see their Table 1). In particular, following Coughlin (2019) (their Equation (51)), in the mildly relativistic regime the shock velocity varies with position as…”
Section: A Mildly Relativistic Decelerating Blast Wave In a Dense Environmentmentioning
confidence: 99%
“…For mildly relativistic shocks we expect the standard ST scaling to hold up to terms that are proportional to V 2 /c 2 ; Coughlin (2019) showed that the coefficient of proportionality multiplying this correction, σ, is a parameter that depends on the post-shock adiabatic index of the gas (effectively equal to 4/3) and the ambient density profile (see their Table 1). In particular, following Coughlin (2019) (their Equation (51)), in the mildly relativistic regime the shock velocity varies with position as…”
Section: A Mildly Relativistic Decelerating Blast Wave In a Dense Environmentmentioning
confidence: 99%
“…Though seeCoughlin (2019) who find evidence supporting validity only up to a shallower value, k max = 18/7 2.57.MNRAS 000, 1-19(2019) …”
mentioning
confidence: 99%
“…Existing data suggest that the LFBOT ejecta were possibly slowly decelerating during the time of observations (e.g., Coppejans et al 2020). Nevertheless, this behavior is not well probed, and the treatment of the deceleration of a mildly relativistic blastwave is not straightforward (Coughlin 2019).…”
Section: Interaction With the Circumstellar Mediummentioning
confidence: 99%